The quantitative analysis of components of fibre-reinforced cement boards. - Kuming, Andrew Paul (My University, 1993)
Environmental and health considerations have led to the substitution of cellulosic fibres for asbestos fibres in many cement-based products. Inevitably, the substitution has required modifications to the manufacturing process. Certain production techniques associated with the switch to cellulosic fibres and other additives needed elucidation. It is possible that to ensure the required concentration of certaln additives in the final product, an excess is being used in the process because of uncertainties about the quantitative balance of the process.
A Research Report submitted to the Faculty of Architecture, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Building.
Keywords: Cement composites.; Fibers.; Asbestos cement.